Moyamoya Syndrome and Congenital Heart Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The association of moyamoya syndrome and congenital heart disease is described in 5 patients at Children's Hospital, Boston, MA.